TANGGAPAN SISWA DAN GURU DI SMAN 1 JAWILAN TENTANG KEBIJAKAN PENGHAPUSAN UJIAN NASIONAL - Mutia; Mutiara Sambella; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
National exams are the main determinant of student graduation in the world. However, there are several countries that have abolished national exams because they are considered unfair by teachers and students. The process and values in learning are not determined by the state but by each school agency, because they are the ones who know how the student proceeds. The purpose of this research was to investigate students' and teachers' responses to the policy of abolishing national exams. The results of this research showed that 62.5% of teachers agreed with various reasons, and 50% of students agreed with the abolition for various reasons.